Social Behavior of Motorcycle Riders at Junior High School Level - Nugroho, Apriyanto Dani; Suyahmo, Suyahmo; Arsal, Thriwaty (Universitas Negeri Semarang, 2017)
Adolescence is considered to be someone’s unstable period. Changing in socio-cultural is seen as complex in todays’ adolescence period. The development of technology and information has shown its influence in social life, one of them is the phenomenon on the use of motorcycle. Nowadays, motorcycle riders are not only dominated by men yet women and adolescences are riding it also. The fact shows that adolescences at junior high school level ride their motorcycle as means of transportation to school. This study is aimed at analysing the background behind the use of motorcycle, describing the readiness in driving motorcycle, and analysing social behaviour created. This study employed qualitative approach. Interview, observation, and document study were used as the data collection techniques. Interactive analysis was used as the data analysis technique. The result showed that it was due to the far distance between home and school, parents’ bustle, unavailability of public transportation, and influence from friends which became the main background of high school students riding motorcycle to school. The readiness of students to drive was low since they did not have driving licence, did not use helmet, and that the proportion of their body and motorcycle was disproportional. Social behaviours which were positively created were trying to be independent, making it easy to cooperatively learn with friends, and accompanying brother(s) to school. Social behaviours which were negatively created were skipping over school, smoking, playing, reckless driving, and making it as lifestyle